EFEKTIFITAS PENGGUNAAN TERAPI CAIRAN INFUS HANGAT DAN BLANKET WARMER PADA PASIEN HIPOTERMI POST ANESTESI REGIONAL DI IBS RSUD KOTA TANGERANG - Restu Gilang Ramadhan (Sekolah Tinggi Pariwisata Mataram, 2023)
Hypothermia is a side effect that can occur following anesthesia. Lower than 36°C body temperature is considered hypothermia. Those recovering from surgery that become hypothermic will tickle as a system defense mechanism. Untreated hypothermia may result in abnormal cardiac rhythms, tachypnea, haemorrhage, shock, increased blood loss, delayed wound healing, and a longer hospital stay. By using a warmer blanket and giving a warm infusion liquid, non-pharmacological treatments are taken using the heating method to prevent hypothermia in the body. To determine the efficacy of using blanket warmers and warm infusion fluid therapeutically on patients receiving post-regional anesthesia at IBS-RSUD Kota Tangerang. Method: This study uses a one-group, quantitative quasi-experiment using with a single group pre-post test design with 68 respondents as the sample. Patients undergoing surgery under regional anesthesia who are adults (>18 years old), have a certain level of attentive mental awareness, can communicate vocally, are not in a life-threatening condition, and are willing to participate in the study are the requirements for inclusion. Following the process replies, the researcher will take their body temperature in the recovery room, after which they will receive an infusion of heated RL fluid or have a blanket warmer attached. In five minutes, fifteen minutes, and thirty minutes following the administration of heated RL fluid and a heating blanket warmer, the researchers once again measured the regional post-anesthesia temperature with a digital axile thermometer. The researchers also considered the ethics of case studies, which included the informed consent of the patient of less than 0.05 percent by considering human discretion and dignity (respect for human dignity), protecting the privacy and confidentiality of the subject of the study (respect for confidentiality), and acquiescence and respect for justice (respect for justice), while considering the benefits and losses incurred. (balancing losses and benefits). Results: There are meaningful changes in the administration of warm infusion warmers and blanket warmers to the increase in the body temperature of patients with post-anesthesia post-regional hypothermia in RSUD of Tangerang City, which demonstrate Wilcoxon's test. The Wilcoxon match pair test obtained a p value < 0,05. Conclusion: There is a meaningful change in the delivery of warmer blankets and hot infusion liquids to increase body temperature in patients with hypothermia post regional anesthesia in the RSUD of Tangerang City